Guide to Assessment Scales in Attention-Deficit/Hyperactivity Disorder Second Edition - Kollins, Scott H.; Sparrow, Elizabeth; Conners, C Keith (Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2010)
A comprehensive guide to the assessment scales, interviews, and questionnaires for ADHD for children, adolescence, and adults. Written by world-renowned experts in psychiatry, specifically in ADHD. Dr Conners' work in this book is invaluable as he is the author of the most widely used assessment scales in the field. A follow-up of the 2003 first edition of the Guide to Assessment Scales in Attention-Deficit Hyperactivity Disorder (also written by Dr Conners and Dr Kollins) Concise analysis of the most useful and popular scales assessing ADHD for children, adolescents, and adults. Explains how to most effectively use the top assessment scales in ADHD for children and adults in the context of a clinical practice Expert commentaries highlight the advantages and disadvantages of each scale, in addition to providing a discussion on how and when to administer them. Attention-deficit hyperactivity disorder (ADHD) is the most commonly studied and diagnosed psychiatric disorder in children, affecting about 3-5% of children globally and diagnosed in about 2-16% of school aged children. Additionally, it is a chronic disorder; 30-50% of individuals diagnosed with ADHD in childhood continue to be symptomatic in adulthood. However, with early diagnosis, medical management and behavioral treatment has been most effective when treating patients with ADHD at any age. Assessment scales are critical and essential tools for the diagnosis and treatment of patients with ADHD. This book has been designed to provide clinicians with a quick guide to the most effective assessment scales in ADHD for patients at any age. Additionally, the scales are used in clinical trials to evaluate drug efficacy.